Bridging Educational Gaps: Challenges and Strategies for Basic Education among Nomadic Pastoralists in North Horr, Marsabit County under SDG 4 - Kalla, Paul Huka (Journal of Education and Practice, 2025)
This study investigated the persistent educational challenges faced by nomadic pastoralist communities in North Horr Constituency, Marsabit County, Kenya, within the framework of Sustainable Development Goal 4 (SDG 4), which advocates for inclusive and equitable quality education for all. Despite Kenya’s progress in expanding educational access, nomadic communities continue to be marginalized due to mobility, harsh environmental conditions, poverty, cultural practices, and inadequate infrastructure. With a school Net enrolment rate far below the national average, North Horr exemplifies the educational divide in arid and semi-arid regions. Guided by Ivan Illich’s Alternative Theory and using a mixed-methods approach, the research explored the status of basic education (Grade 1–9). The respondents of the study consisted of pupils, teachers, head teachers, education officials, administrators, parents and village elders. The data collection instruments included questionnaires, interview guides, focus group discussion and document analysis. The study identified key barriers to access, and proposes context-specific strategies. These include the establishment of feeder and mobile schools, flexible teaching schedules, integration of formal education into religious institutions, and the use of technology for remote learning. The findings aim to inform policy and practice, ensuring education systems are more adaptive, inclusive, and culturally sensitive to the needs of nomadic populations in Kenya.